การใช้ประโยชน์เถ้าลอยชานอ้อยในการดูดซับสารไฮโดรคาร์บอนที่ปนเปื้อนในน้ำ - อภิญญา นิลยอง (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Utilization of bagasse fly ash, a waste from biomass power plant, as an adsorbent for adsorption of polycyclic aromatic hydrocarbons (PAHs) contamination in water was investigated and presented in this paper. The bagasse fly ash (BFA) was collected from a sugar industry of Thailand. Chemical composition of the BFA characterized by X-Ray Fluorescence shows SiO2 as a major content. Therefore, it is expected to be utilized as an alternative adsorbent and/or silica raw material. BFA as well as silica extracted from the BFA, with and without surface treatment, was comparatively investigated for adsorption of PAHs contamination in water by using naphthalene as a PAHs representative, and cetyltrimethylammoniumbromide (CTAB) as a surface treating agent. Adsorption efficiency affected by various factors, such as effect of shaking rate, shaking time, solution pH, and adsorbent-naphthalene weight ratio were comparatively investigated. Results of the study indicated that all adsorbents exhibited similar adsorption efficiency when using naphthalene initial concentration of 10 mg/l at pH 2-10, shaking with 0.4-1.0 weight ratios of each adsorbent at 100-250 rpm for 10-100 minutes. An optimize condition for all adsorbents were observed to be using 0.4 g adsorbent in 100 ml of 10 mg/l naphthalene solution (except the case of BFA without surface treatment was observed to be 0.7-0.8 weight ratios) at pH 2 and shaking the solution at 250 rpm for 40 minutes. Both Freundlich and Langmuir isotherms was observed to fit with data for the naphthalene adsorption with either BFA treated with hydrogen peroxide or silica from BFA treated with CTAB. Hence, the adsorption behavior is considered as both monolayer and multilayer